Virulence Factors and Molecular Identification of Candida Species Causing Candidemia in Honduras - José Fernando Chávez; Bryan Ortiz; Roque López; Carlos Muñoz; Kateryn Aguilar; Isis Laínez-Arteaga; Celeste Galindo; Luis Rivera; Manuel G. Ballesteros-Monrreal; Kathy Montes; Mauricio Hernández; Asly Villeda Barahona; et al. (Journal of Fungi, 2025)
Invasive fungal infections (IFIs), primarily caused by Candida species, represent a significant global public health concern due to their high mortality rates and growing antifungal resistance. In Honduras, data on their epidemiology remains scarce. This study aimed to characterize Candida species associated with candidemia and assess key virulence factors. A total of 80 clinical isolates were collected from four hospitals in Honduras’s major cities, Tegucigalpa and San Pedro Sula. Identification was performed using both phenotypic and molecular methods. Hemolytic activity, phospholipase and protease production, and biofilm formation were evaluated. C. albicans and C. tropicalis were the most prevalent species (30% each), followed by C. parapsilosis (27.5%). Phenotypic methods misidentified 13.8% of the isolates. Most strains (96.3%) exhibited strong hemolytic activity. C. albicans showed the highest phospholipase activity, while C. tropicalis was the most robust film producer. These findings highlight an evolving epidemiological landscape characterized by an increasing prevalence of non-albicans Candida species, often less susceptible to antifungal agents, and diverse virulence profiles such as strong biofilm formation. This underscores the clinical need for accurate species-level identification through molecular diagnostics and ongoing surveillance to guide targeted antifungal therapy and enable early, locally adapted interventions.